A year in the life of a mountain pine beetle - Aguayo, Ingrid, author; Mason, Lisa, author; Leatherman, Dave, author; Bonnell, Mary Ann, artist; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2007)
This book by "Buford, the mountain pine beetle" is aimed at children to give them an understanding of the mountain pine beetle and its role in our forests.
The characters Buford and Bernadette were created by Dave Leatherman.
Illustrations by Mary Ann Bonnell.